2017 IEEE International Workshop on Signal Processing Systems (SiPS) 2017
DOI: 10.1109/sips.2017.8110006
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal cardiovascular information monitor using piezoelectric transducers for wearable healthcare

Abstract: This article describes a multimodal cardiovascular information measurement method using a wearable device composed of piezoelectric transducers. Cardiovascular diseases are increasing with the aging population, and they constitute a significant portion of the causes of death and long-term care. In recent years, daily-life monitoring using wearable sensor devices has attracted particular attention for the prevention and early detection of cardiovascular diseases. However, recent wearable devices can only measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Liu et al found that the multimodal sensor device was easy to operate and could quickly obtain stable and reliable physiological information [103]. Similarly, Okano et al measured multimodal data to monitor cardiovascular information using a wearable device at the wrist, such as HRV, PWV, and blood flow velocity [104]. The multi-modality analysis can enrich the physiological value of the radial pulse wave.…”
Section: ⅵ Discussionmentioning
confidence: 99%
“…Liu et al found that the multimodal sensor device was easy to operate and could quickly obtain stable and reliable physiological information [103]. Similarly, Okano et al measured multimodal data to monitor cardiovascular information using a wearable device at the wrist, such as HRV, PWV, and blood flow velocity [104]. The multi-modality analysis can enrich the physiological value of the radial pulse wave.…”
Section: ⅵ Discussionmentioning
confidence: 99%
“…Heart rate monitoring is of great importance in preventing disease. Increasing medical costs due to increased patients with noncommunicable diseases (NCD) have become a critical problem worldwide 4 . One of the main NCDs is cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse signals are generated by the periodic contraction and relaxation of the heart muscle, and it is deeply affected by cardiovascular status. Thus, pulse signals contain various pieces of physiological information and have already been widely adopted in Western clinical examinations [ 1 ] and traditional Chinese medicine [ 2 ]. Monitoring detailed pulse information in real time can significantly reduce accidents due to cardiovascular problems in individuals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%